Taking stock: UK national antidote availability increasing, but further improvements are required. Issue 3 (18th November 2015) - Bailey, GP; Rehman, B; Wind, K; Wood, DM; Thanacoody, R; Nash, S; Archer, JRH; Eddleston, M; Thompson, JP; Vale, JA; Thomas, SHL; Dargan, PI
Abstract : Background: A 2010/2011 audit of the Royal College of Emergency Medicine (RCEM) National Poisons Information Service (NPIS) UK guidelines on antidote availability demonstrated variable stocking of antidotes for the management of poisoned patients; the guidelines were updated and republished in 2013. Aim: To assess if antidote stocking has improved since the 2010/2011 audit and introduction of the 2013 guidelines. Methods: Questionnaires were sent to Chief Pharmacists at all 215 acute hospitals in England, Wales and Northern Ireland in October 2014. Data were collected on the timing of availability (category A antidotes should be available immediately, category B within 1 h and category C can be held supraregionally) and stock levels. Results: 169 (78.6%) responses were received. Atropine, calcium gluconate and flumazenil (category A) were the only antidotes available in all hospitals within the recommended time and stock levels. Forty-one (24.3%) hospitals held every category A antidote; this increased to 81 (47.9%) for those holding at least one cyanide antidote and all other category A antidotes. The proportion of hospitals stocking category A/B antidotes within the recommended time increased for 20 (90.9%) category A/B antidotes. Fomepizole (category B) availability increased to 62.1% of hospitals from 11.4% in 2010/2011. Other than penicillamine (63.3% hospitals), there was poor availability (2.4%–36.1%) of category C antidotes. Conclusions: Availability of category A and B antidotes has improved since the 2010/2011 audit and 2013 guidelines. However, there remains significant variability particularly for category C antidotes. More work is required to ensure that those treating poisoned patients have timely access to antidotes focusing particularly on category C antidotes.